The importance of surfactant volumes of islands glaciers of Antarctic coast like climate changes indicator - K. R. Tretiak; V. M. Hlotov; Yu. I. Holubinka (Ukrainian Antarctic Journal, 2013)
In this article the results of volumes determination of islands glaciers of Argentinian archipelago (West Antarctic) are shown. For this purpose two methods were used: ground laser scanning and digital photogrammetry measurements.